2002
DOI: 10.1897/1551-5028(2002)021<2365:muaero>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Uptake and Enzymatic Response of Posidonia Oceanica After an Experimental Exposure to Organic and Inorganic Forms

Abstract: The aim of this study was to examine the experimental uptake of mercury and the enzymatic response, i.e., glutathione S-transferase (GST) activity, to this metal introduced into the medium under organic (methylmercury chloride) and nonorganic (mercury chloride) forms. Shoots of Posidonia oceanica were collected in a nonpolluted area in the northwestern Mediterranean Sea and were treated in aquaria with increasing mercury concentrations/exposure times (48, 96, and 144 h). Compared with the controls, a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…At least five seagrass species have been found to bioconcentrate mercury at concentrations between 4 and 51,500 ng/g dry weight. Nonorganic mercury was more bioavailable to P. oceanica than organic mercury in a laboratory exposure and glutathione-S-transferase activity significantly increased in some tissues as mercury uptake increased [74]. Organic mercury was at least 50% of the total mercury bioconcentrated in that study.…”
Section: Seagrass Tissuesmentioning
confidence: 57%
“…At least five seagrass species have been found to bioconcentrate mercury at concentrations between 4 and 51,500 ng/g dry weight. Nonorganic mercury was more bioavailable to P. oceanica than organic mercury in a laboratory exposure and glutathione-S-transferase activity significantly increased in some tissues as mercury uptake increased [74]. Organic mercury was at least 50% of the total mercury bioconcentrated in that study.…”
Section: Seagrass Tissuesmentioning
confidence: 57%
“…Although many studies have highlighted the usefulness of P. oceanica as a recorder of ambient trace metal pollution (Maserti et al, 1988;Catsiki and Panayotidis, 1993;Malea, 1993;Malea et al, 1994;Warnau et al, 1995;Pergent-Martini, 1998;Delgado et al, 1999;Ferrat et al, 2002;Ancora et al, 2004;Balestri et al, 2004;Gosselin et al, 2006), much less information is available regarding the content of organic contaminants in this seagrass. However, the few studies that have reported on bioaccumulation of organic contaminants in P. oceanica tissues (e.g., Viso et al, 1993;Lewis and Devereux, 2009;Pergent et al, 2011) highlight the potential of this plant to serve as an indicator of organic pollutants in the Mediterranean Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Following this disaster, most concern has centred on the presence of mercury in fish, and extensive surveys have been carried out in a number of countries to evaluate the presence of mercury in aquatic biota (Monteiro et al 1996;Nakagawa et al 1997;Pergent and Pergent-Martini 1999;Sanchiz et al 1999;Frodello et al 2000;Pirrone et al 2001;Ferrat et al 2002Ferrat et al , 2003Storelli et al 2002;Love et al 2003;Kucuksezgin et al 2006). However, only one study concerning the gulf of Gabes has been published to date (Hadj Ali et al 1986).…”
Section: Introductionmentioning
confidence: 99%